Performance analysis in won and lost matches and the predictors of goal difference and match outcome in Women’s Handball European Championship 2022 - Paweł Krawczyk; Anna Kupczak; Joanna Pergoł; Aleksandra Julia Hejnosz (Scientific Reports)
Abstract The aim of this study is determine whether there are differences in performance analysis in matches won and lost at the 2022 European Women’s Handball Championship, and which actions are predictors of goal difference and match outcome. The analysis included 44 matches. The Student’s t-test and the Mann-Whitney U test was used to examine differences between winning and losing matches. Multivariate regression and logistic regression analysis was used to determine predictors of goal differences, and match outcome. Winning teams perform fewer positional attacks (d = 0.51) and more fast breaks (η2 = 0.01). Winning teams score significant higher number of goals in attack (d = 1.43), positional attack (d = 1.11), and have a higher efficiency of attack (d = 1.71) and positional attack (η2 = 0.39) throwing. Goalkeepers in winning matches make a significant higher number of defenses (d = 0.79) and have higher overall efficiency (d = 1.27). Predictors of goal differential (increasing it) in matches is efficiency of positional attack (β = 0.61), fast break (β = 0.28), and goalkeeper defenses (β = 0.46). The effectiveness of the attack (OR = 1.55) and goalkeeper’s defenses (OR = 1.24) increase the probability of winning the match, while the number of shots from 9 m (OR = 0.80) decreases it. Specialized handball training should be optimized to increase the number and effectiveness of team and individual actions, which differentiate the outcome of the match.